2010
DOI: 10.1007/s10266-009-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of antiangiogenic gene therapy targeting VEGF in oral cancer

Abstract: It is well known that tumor angiogenesis plays an important role in local growth and metastasis of oral cancer; therefore, inhibiting angiogenesis is considered to be effective for treating oral cancer. This study aimed to investigate the effectiveness of systemically available antiangiogenic gene therapy targeting vascular endothelial growth factor (VEGF), which is one of the most important angiogenesis accelerators. We administered a soluble form of VEGF receptor-expressing gene incorporated into adenovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…HSC-3 cells in Eagle's minimum essential medium (Sigma-Aldrich, St Louis, MO, USA) supplemented with 10% fetal bovine serum (Sigma-Aldrich) and 1000 units/mL penicillin/streptomycin solution (Sigma-Aldrich) were routinely cultured in an incubator in 5% CO 2 at 37°C. Trypsin (0.25%) and ethylenediaminetetraacetic acid (0.02%; Sigma-Aldrich) solution was used to isolate cells for subculture, as previously described [16].…”
Section: Methodsmentioning
confidence: 99%
“…HSC-3 cells in Eagle's minimum essential medium (Sigma-Aldrich, St Louis, MO, USA) supplemented with 10% fetal bovine serum (Sigma-Aldrich) and 1000 units/mL penicillin/streptomycin solution (Sigma-Aldrich) were routinely cultured in an incubator in 5% CO 2 at 37°C. Trypsin (0.25%) and ethylenediaminetetraacetic acid (0.02%; Sigma-Aldrich) solution was used to isolate cells for subculture, as previously described [16].…”
Section: Methodsmentioning
confidence: 99%
“…No DNA ladder was detected in Gin-1 treated with 0.2 M and Ltd, Tokyo, Japan) during admission to neurosurgery 5) . Since…”
Section: Detection Of Apoptosismentioning
confidence: 90%
“…In those experiments, on the other hand, glycerol in isolation has not been considered to inhibit growth and invasion of cancer cell lines 4) . However, inhibition of tumor growth was observed after glycerol was administrated to a patient with oral cancer complicated by cerebral infarction 5) , suggesting a tumor-inhibitory effect of the sole administration. Thus, the present study aimed to clarify to what extent separate administration of glycerol inhibited growth and invasion of cancer cell lines and how the inhibitory mechanisms worked.…”
Section: Introductionmentioning
confidence: 99%
“…57 Angiogenesis is a crucial step in the processes of uncontrolled tumor proliferation and metastasis, and inhibiting angiogenesis is considered to be effective for treating oral cancer. Vascular endothelial growth factor (VEGF) is thought to be an important angiogenic factor, 58 and studies have shown that OSCC is associated with an elevated VEGF concentration in the serum. These higher levels of VEGF are correlated with lymph node metastasis, clinical stage, and the prognosis and treatment of OSCC.…”
Section: Pathophysiology Of Oral Cancermentioning
confidence: 99%